2022
DOI: 10.1111/cas.15469
|View full text |Cite
|
Sign up to set email alerts
|

M6A demethylase fat mass and obesity‐associated protein regulates cisplatin resistance of gastric cancer by modulating autophagy activation through ULK1

Abstract: Drug resistance is an important factor for treatment failure of gastric cancer. N 6 ‐methyladenosine (m 6 A) is the predominant mRNA internal modification in eukaryotes. The roles of m 6 A modification in drug resistance of gastric cancer remains unclear. In the present study, the m 6 A methylated RNA level was significantly decreased while the expression of m 6 A demethylase fat mass and obesity‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…Jin et al [66] demonstrated that FTO can specifically upregulate the ULK1 protein level via m 6 A mediated demethylation, thereby promoting the activation of autophagy. Similarly, Zhang et al also reported that FTO promotes cisplatin resistance by facilitating autophagy by targeting ULK1 via an m 6 A-dependent manner in gastric cancer cells [67]. Moreover, the downregulation of FTO suppressed the expression of ATG5 and ATG7, inhibiting autophagosome formation, thereby restaining autophagy and adipogenesis [68].…”
Section: Ftomentioning
confidence: 91%
“…Jin et al [66] demonstrated that FTO can specifically upregulate the ULK1 protein level via m 6 A mediated demethylation, thereby promoting the activation of autophagy. Similarly, Zhang et al also reported that FTO promotes cisplatin resistance by facilitating autophagy by targeting ULK1 via an m 6 A-dependent manner in gastric cancer cells [67]. Moreover, the downregulation of FTO suppressed the expression of ATG5 and ATG7, inhibiting autophagosome formation, thereby restaining autophagy and adipogenesis [68].…”
Section: Ftomentioning
confidence: 91%
“…Thus, METTL3 inhibits autophagy to enhance anticancer drug sensitivity. The expression of FTO was increased in cisplatin-resistant (SGC-7901/DDP) gastric cancer cells [ 166 ]. The downregulation of FTO reversed cisplatin resistance in SGC-7901/DDP cells, which was attributed to the inhibition of (ULK1)-mediated autophagy ( Figure 3 C) [ 166 ].…”
Section: The Roles Of Mettl3 In Anticancer Drug Resistance and Autophagymentioning
confidence: 99%
“…The expression of FTO was increased in cisplatin-resistant (SGC-7901/DDP) gastric cancer cells [ 166 ]. The downregulation of FTO reversed cisplatin resistance in SGC-7901/DDP cells, which was attributed to the inhibition of (ULK1)-mediated autophagy ( Figure 3 C) [ 166 ]. Thus, high levels of m6A enhance the sensitivity of cancer cells to cisplatin by inhibiting autophagy.…”
Section: The Roles Of Mettl3 In Anticancer Drug Resistance and Autophagymentioning
confidence: 99%
“…Autophagy is an auto‐catabolic process that permits cells to deal with stress‐coping strategies by degrading damaged organelles and accumulated proteins, which could result in cancer resistance treated with anticancer drugs 85–89 . LncRNA regulates cell autophagy and contributes to chemoresistance.…”
Section: Mechanisms Underlying Cancer Drug Resistancementioning
confidence: 99%